(untitled) (International Seven Journal of Health Research, 2023)
Objective: To identify the scientifically proven benefits of practicing and adhering to SMA for the binomial. Methods: Integrative literature review in the databases Scientific Electronic Library Online (SciELO), Latin American and Caribbean Literature in Health Sciences (LILACS), Virtual Health Library (VHL), including articles published between 2017 and 2021. The descriptors "breastfeeding", "weaning", "disease prevention" and "health promotion" were used. Results: The final sample consisted of 18 articles, the majority of which addressed the aspects that permeate and collaborate for an adequate breastfeeding practice and also the benefit of its use from short to long term to the binomial. Final considerations: The practice of exclusive breastfeeding is influenced by various factors, including social, economic, cultural, ethnic and psychological aspects. This practice is responsible for generating numerous benefits for mother and baby, such as promoting a healthy gastrointestinal (GI) microbiome in the newborn, better cognitive performance, immunity and also contributing to the maturation and proper development of the orofacial musculature. For the nursing mother, it prevents bleeding and neoplasms.